Sensing controlled pulse key-holing condition in plasma arc welding - 贾传宝 武传松 张裕明 (Transactions of Nonferrous Metals Society of China, 2009)
According to the strategy of controlled pulse key-holing, a new sensing and control system was developed for monitoring and controlling the keyhole condition during plasma arc welding （PAW）. Through sensing and processing the efflux plasma voltage signals, the quantitative relationship among the welding current, efflux plasma voltage and backside weld width of the weld was established. PAW experiments show that the efflux plasma voltage can reflect the state of keyhole and backside weld width accurately The closed-loop control tests validate the stability and reliability of the developed keyhole PAW system.